2016
DOI: 10.1371/journal.pone.0168974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Milk Replacer Ad Libitum or in Restricted Amounts for the First Five Weeks of Life on the Growth, Metabolic Adaptation, and Immune Status of Newborn Calves

Abstract: The pre-weaning period is critical for calf health and growth, and intensive milk feeding programs may assist postnatal development by improving body growth and organ maturation. The aim of the present work was to study the effects of ad libitum milk replacer (MR) feeding on the growth, metabolic adaptation, health, and immune status of newborn calves. Twenty-eight newborn Holstein and Holstein x Charolais crossbred calves were fed ad libitum (ADLIB) or in restricted amounts (6 liters per day; RES) during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 89 publications
4
46
2
3
Order By: Relevance
“…Similar results for globulin and total protein concentrations have been observed where calves were offered restricted compared with an unlimited milk allowance (Hammon et al 2002). Several studies including a recent report by Schäff et al (2016) have shown that systemic concentrations of albumin increase steadily in the weeks after birth. In our study, we observed a steady increase in concentrations of albumin over time in HIGH calves, with greater concentrations compared to their contemporaries on LOW during the post-weaning period.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results for globulin and total protein concentrations have been observed where calves were offered restricted compared with an unlimited milk allowance (Hammon et al 2002). Several studies including a recent report by Schäff et al (2016) have shown that systemic concentrations of albumin increase steadily in the weeks after birth. In our study, we observed a steady increase in concentrations of albumin over time in HIGH calves, with greater concentrations compared to their contemporaries on LOW during the post-weaning period.…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, feeding a high level of milk resulted in higher levels of IGF-1 detected at wk 1 until wk 5 and a tendency for an increased concentration of IGF-1 at wk 7. It has been previously shown that elevated feeding of nutrients from milk replacer preweaning increases IGF-1 (Bartlett et al, 2006;Daniels et al, 2008;Schaff et al, 2016); however, a noteworthy difference in our findings is a detectable difference in IGF-1 at wk 1 of life. Schaff et al (2016) fed an elevated level of milk replacer for the first 5 wk of life, and despite differences in actual milk intake and ME intake among their calves fed a high versus a low plane of nutrition from wk 1, a difference in IGF-1 was not observed until 29 d.…”
contrasting
confidence: 85%
“…In addition, with no maximum per visit, the calf has more flexibility as to when it receives milk. Similarly, Schaff et al (2016) indicated that calves were allowed to consume 2 L per visit with no explanation of what the minimum amount was. Because of this, it is plausible that calves were visiting the calf feeder when they had accumulated from 0.5 to 2.0 L, which is less restrictive on when calves consume and how much they get per day.…”
mentioning
confidence: 99%
“…The results demonstrated that intake of solid feed and weight gain increased during weaning in calves fed elevated amounts of milk and weaned through the step-down method compared with those fed milk conventionally. More recent studies (Schäff et al, 2016(Schäff et al, , 2018 have also used the "step-down" method by feeding MR (125 g of MR powder per L) ad libitum for 5 wk, followed by reduction in MR proportionally day by day to 6 L of MR at wk 7 compared with calves fed only 6 L until weaning to investigate growth, metabolic adaptation, health, and rumen and small intestinal growth. The benefits reported in this study were greater perirenal fat and muscle mass and increased anabolic metabolism (as indicated by increased insulin-like growth factor 1 concentration in blood) for step-down calves compared with those who had restricted amounts of milk.…”
Section: Weaning Strategiesmentioning
confidence: 99%